Putative Novel Effector Genes Revealed by the Genomic Analysis of the Phytopathogenic Fungus Fusarium oxysporum f. sp. physali (Foph) That Infects Cape Gooseberry Plants - Simbaqueba, Jaime; Rodríguez, Edwin A.; Burbano-David, Diana; González, Carolina; Caro-Quintero, Alejandro (Frontiers in Microbiology, 2021)
The vascular wilt disease caused by the fungus Fusarium oxysporum f. sp. physali (Foph) is one of the most limiting factors for the production and export of cape gooseberry (Physalis peruviana) in Colombia. A previous study of the transcriptomic profile of a highly virulent strain of F. oxysporum in cape gooseberry plants, from a collection of 136 fungal isolates obtained from wilted cape gooseberry plants, revealed the presence of secreted in the xylem (SIX) effector genes, known to be involved in the pathogenicity of other F. oxysporum formae speciales (ff. spp.). This pathogenic strain was named Foph, due to its specificity for cape gooseberry hosts. Here, we sequenced the genome of Foph, using the Illumina MiSeq platform. We analyzed the assembled genome, focusing on the confirmation of the presence of homologues of SIX effectors and the identification of novel candidates of effector genes unique of Foph. By comparative and phylogenomic analyses based on single-copy orthologues, we identified that Foph is closely related to F. oxysporum ff. spp., associated with solanaceous hosts. We confirmed the presence of highly identical homologous genomic regions between Foph and Fol, that contain effector genes and identified seven new effector gene candidates, specific to Foph strains. We also conducted a molecular characterization of a panel of 29 F. oxysporum additional stains associated to cape gooseberry crops isolated from different regions of Colombia. These results suggest the polyphyletic origin of Foph and the putative independent acquisition of new candidate effectors in different clades of related strains. The novel effector candidates identified by sequencing and analyzing the genome of Foph, represent new sources involved in the interaction between Foph and cape gooseberry. These resources could be implemented to develop appropriate management strategies of the wilt disease caused by Foph in the cape gooseberry crop.